Malposition of a Femoral Tunneled Dialysis Catheter through a Patent Foramen Ovale - Blackburn, Anthony Finnay; Landinez, Gina P.; Kerlan, Robert K.; Lokken, R. Peter (Seminars in Interventional Radiology, 2023)
Patent foramen ovale (PFO) is a common congenital abnormality of high prevalence in adults. Its clinical significance is magnified in a right-to-left shunt, where paradoxical embolism can have catastrophic outcomes involving the brain, heart, mesenteric circulation, or extremities. Right-to-left shunting through a PFO is caused by increased right atrial pressure, as seen in the setting of pulmonary artery hypertension or pulmonary embolism. This case highlights the relevance of central venous catheter placement in the setting of a PFO. While the patient did not experience clinical sequelae from line placement, she was at high risk for paradoxical embolus. Recognizing the possibility of a PFO during central venous catheter placement, especially in the setting of increased right pressures, should be a consideration of all interventional radiologists.
Keywords: tunneled dialysis catheter; malposition; patent foramen ovale; right-to-left shunt